Evaluation of the Protective Effect of Ethanol Extract of Acalypha indica Leaf Against Paracetamol- Induced Liver Dysfunction - MATHEW, MOLLY; JOY, BEENA (Asian Journal of Chemistry, 2010)
A number of medicinal plants, traditionally used for many years, in the treatment of liver ailments, are available in the tropical and subtropical regions. One such plant, Acalypha indica, though widely used by tribal people, is not much investigated therapeutically. Hence an effort was made to evaluate the hepatoprotective activity of the ethanol extract of the leaves of Acalypha indica in male albino rats of average weight (100-120 g) using paracetamol as hepatotoxicant (3 g/kg). As 100 mg was identified as the optimum dose to exert the said effect, this dose was selected for the programmed study. Silymarin was used as a reference standard. Levels of marker enzymes like aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatase (ALKP) total protein (TP), albumin (Alb) and total bilirubin (T.Bil) were estimated in serum. A probe into the mechanism of action was attempted by estimating the thiobarbituric acid reactive substances (TBARS) and glutathione (GSH) levels in liver homogenates in order to evaluate the degree of lipid peroxidation. Histopathological studies were also done to confirm the biochemical changes. Acalypha indica extract produced substantial improvement in hepatocellular function as evidenced by reversal of ballooning degeneration and sinusoidal congestion. It also showed reversal of important enzyme functions of liver which were comparable to the effects of silymarin.